Beyond the binaries: reshaping pain communication through arts workshops. Issue 3 (13th February 2018) - Tarr, Jen; Cornish, Flora; Gonzalez‐Polledo, Elena
Abstract: Pain is difficult to communicate and translate into language, yet most social research on pain experience uses questionnaires and semi‐structured interviews that rely on words. In addition to the mind/body dualism prevalent in pain medicine in these studies pain communication is characterised by further value‐laden binaries such as real/unreal, visible/invisible, and psychological/physical. Starting from the position that research methods play a role in constituting their object, this article examines the potential of participatory arts workshops for developing different versions of pain communication. Twenty‐two participants were involved in workshops using drawing, digital photography, sound and physical theatre to explore pain communication. The use of arts materials made pain tangible. By manipulating pain‐related objects, participants could consider alternative relationships to their pain. Pain's sociality was also explored, with relations with clinicians and others emerging as potentially cooperative rather than adversarial. Discussions considered whether pain felt internal or external, and whether it was possible to conceive of a self without pain. We argue that the socio‐material context of participatory arts workshops enabled these alternative versions of pain. Such methods are a useful addition to medical sociology's heavy reliance on qualitative interviewing.